ULK3-dependent activation of GLI1 promotes DNMT3A expression upon autophagy induction. Issue 12 (2nd December 2022) - González-Rodríguez, Patricia; Cheray, Mathilde; Keane, Lily; Engskog-Vlachos, Pinelopi; Joseph, Bertrand
ABSTRACT: Macroautophagy/autophagy is a tightly regulated catabolic process, which contributes at baseline level to cellular homeostasis, and upon its stimulation to the adaptive cellular response to intra- and extracellular stress stimuli. Decrease of autophagy activity is occurring upon aging and thought to contribute to age-related-diseases. Recently, we uncovered, upon autophagy induction, the role of de novo DNMT3A (DNA methyltransferase 3 alpha)-mediated DNA methylation on expression of the MAP1LC3 (microtubule associated protein 1 light chain 3) proteins, core components of the autophagy pathway, which resulted in reduced baseline autophagy activity. Here, we report that serine/threonine kinase ULK3 (unc-51 like kinase 3)-dependent activation of GLI1 (GLI family zinc finger 1) contributes to the transcriptional upregulation of DNMT3A gene expression upon autophagy induction, thereby bringing additional understanding of the long-term effect of autophagy induction and a possible mechanism for its decline upon aging, pathological conditions, or in response to treatment interventions. Abbreviations: CBZ: carbamazepine; ChIP: chromatin immunoprecipitation; Clon: clonidine; DNMT3A: DNA methyltransferase 3 alpha; GLI1: GLI family zinc finger 1; GLI2: GLI family zinc finger 2; MAP1LC3: microtubule associated protein 1 light chain 3; MTOR: mechanistic target of rapamycin kinase; PLA: proximity ligation assay; RT-qPCR: quantitative reverse transcription PCR; shRNA: small hairpin RNA; siRNA: small interfering RNA; Treh: trehalose; ULK3: unc-51 like kinase 3.